IMPLEMENTASI FLIP LEARNING STRATEGI MENINGKATKAN HIGHER ORDER THINKING MAHASISWA - Rani Sofya (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2018)
The Millennium Era gave birth to a generation called "digital native". Students in the millenial era in everyday familiar with the digital world. Educators must be creative in implementing learning for digital natives, so that learning activities do not become boring activities for them. One of the learning strategies that teachers can use is Flip Learning. Researchers collect some literature to formulate the steps of application Flip Learning. Flip learning has been applied to many countries and research results show that flip learning can increase student engagement, student motivation and student learning outcomes. The application of Flip learning is done with teachers providing material access through video, powerpoint, or digital books, or other resources to learn outside the classroom. In the classroom, students are actively involved in small group discussions as well as large groups and problem solving activities. Through students engagements  in the learning process that requires them to construct their in-depth knowledge and it can  improve their higher order thinking.